Educación intercultural y aprendizaje significativo: un reto para la educación básica en la Escuela de Educación General Básica “Pedro de Cianca” - Yaruquí Paltín, Gabriela Yasmín (2022)
Considering the need to provide quality education and generate significant learning within the pedagogical processes, it is fundamentally important to implement teaching strategies on intercultural education. The general aim of this study was to generate a proposal to incorporate intercultural education in the General Basic Education School "Pedro de Cianca" oriented to generate significant learning. It had the following specific objectives: To characterize intercultural education as a means to generate significant learning in the teaching process. To analyze the methodological models and strategies that integrate intercultural education in the pedagogical processes of basic education and to propose teaching-learning strategies that integrate intercultural education to generate significant learning. The study was proposed with a mixed methodological approach of correlational type and the use of methods such as: hermeneutic, documentary, analytical, statistical and observation technique, carrying out interview and survey instruments, with the participation of 30 students from 2nd to 7th year and two teachers. Among the most relevant results, it was determined that the pedagogical models taught by the teachers have not responded to the educational needs of the students, since most of the children have not developed a sense of social belonging and maintain a certain terminological confusion about the cultural group to which they belong, which prevents self-identification and generates the loss of their cultural identity, Therefore, it is concluded that teachers should integrate intercultural education strategies into their pedagogical processes in order to provide a pedagogical response that meets the requirements of the cultural diversity of the students and adjusts to the emerging demand that education needs so much in the challenge of building inclusive schools that have as a fundamental pillar the acceptance and recognition of cultural diversity. Key words: Intercultural education, Meaningful learning, Active teaching-learning strategies, Cultural diversity.